2020
DOI: 10.1155/2020/3248294
|View full text |Cite
|
Sign up to set email alerts
|

Change in the Mechanic Properties and Electrical Resistivity of High Water Backfill Material under Electrochemical Treatment

Abstract: To modify the mechanic properties of high water backfill material (HWBM) for its engineering application in mining backfill, a series of experiments were performed to investigate the effects of electrochemical treatment on the mechanic properties and electrical resistivity of the HWBM at the early age. Meanwhile, the effects of the potential gradient, power-on time, and water–cement ratio (W/C) on electrochemical modification efficiency were investigated. The results show that the uniaxial compression strength… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…Previous studies have shown that the water–cement ratio and the content of impurities influence HWBMs [ 32 , 33 ]. Guodong Li et al [ 34 , 35 ] used the HWBM from Yangzhou China Mining Construction New Material Technology Co., Ltd. (Yangzhou, China), selected the water–cement ratio of the HWBM to be 1, 1.5 and 2, set the desert sand doping amount to be 0, 30%, and 60%, and made seven types of desert sand-based filling material samples.…”
Section: Experimental Studymentioning
confidence: 99%
“…Previous studies have shown that the water–cement ratio and the content of impurities influence HWBMs [ 32 , 33 ]. Guodong Li et al [ 34 , 35 ] used the HWBM from Yangzhou China Mining Construction New Material Technology Co., Ltd. (Yangzhou, China), selected the water–cement ratio of the HWBM to be 1, 1.5 and 2, set the desert sand doping amount to be 0, 30%, and 60%, and made seven types of desert sand-based filling material samples.…”
Section: Experimental Studymentioning
confidence: 99%